ANALISIS UJI IMPAK DAN MIKROSTRUKTUR KOMPOSIT MATRIKS RESIN POLYESTER BERPENGISI CANGKANG TELUR AYAM KAMPUNG - Asmeati; Muhammad Yusuf Ali; Muhammad Syahrir; Riswandi (Jurnal Sosial dan Teknologi Terapan AMATA, 2024)
Along with the advancement of science and technology, composite materials have developed rapidly. The emergence of new materials is a breakthrough in composite technology. Many wastes around us can be used as materials that can increase the toughness of composites such as chicken egg shells. This study was conducted to determine the toughness and microstructure of composites with variations in the volume fraction of chicken egg shells mixed with polyester resin. The variations in the volume fraction are 10%, 20% 30%, 40%, 50%, and 100% resin (without shells). The specimen tests of this study were impact tests and SEM tests. The results of the study stated that the highest impact test value was found in the 30% fraction variation, namely 19,163 KJ / m2 and the lowest impact test value was found in the 100% fraction variation without egg shell mixture with a value of 4,409 KJ / m2. SEM testing found the particle shape, almost single round shape and lumps with sizes of 2.99 to 16.8 μm and found agglomeration and nano particles have different sizes, there are pores due to wind entering and becoming bubbles when drying the specimen which causes low impact test values. Keyword: Chicken egg shells, Composite, Polyester Resin, Impact, Microstructure